2009
DOI: 10.1128/aac.01231-08
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam and Fluoroquinolone Combination Antibiotic Therapy for Bacteremia Caused by Gram-Negative Bacilli

Abstract: The role of combination antibiotic therapy with a beta-lactam and a fluoroquinolone for bacteremia caused by gram-negative bacilli, to our knowledge, has not been previously described. Much of the previous study of combination therapy has included beta-lactams and aminoglycosides. We conducted a large retrospective cohort study to evaluate 28-day all-cause mortality in patients with monomicrobial bacteremia due to aerobic gram-negative bacilli who received either a combination of beta-lactams and fluoroquinolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 30 publications
2
46
0
3
Order By: Relevance
“…c Typically require dual broad-spectrum antibiotics with overlapping coverage [189][190][191][192]. d In patients with a history of IV drug use, those with indwelling vascular catheters or devices, or those with recent hospitalizations an agent such as daptomycin (in absence of pneumonia) or vancomycin (IF mic ≤1) or linezolid (in absence of bacteremia) should be adopted.…”
Section: Late Onset And/or Risk Factors For Mdr Organismsmentioning
confidence: 99%
“…c Typically require dual broad-spectrum antibiotics with overlapping coverage [189][190][191][192]. d In patients with a history of IV drug use, those with indwelling vascular catheters or devices, or those with recent hospitalizations an agent such as daptomycin (in absence of pneumonia) or vancomycin (IF mic ≤1) or linezolid (in absence of bacteremia) should be adopted.…”
Section: Late Onset And/or Risk Factors For Mdr Organismsmentioning
confidence: 99%
“…[1][2][3][4][5] Population-based studies that specifically address the epidemiology and outcome of Klebsiella spp BSI are lacking because most previous studies have been derived from referral tertiary care centers. [6][7][8] Therefore, we performed a population-based study to determine the incidence rate of Klebsiella spp BSI and to investigate for temporal changes and seasonal variation in the incidence rate of Klebsiella spp BSI.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…A general combination therapy comprising two (or more) broad-spectrum antibiotics cannot be recommended due to the inconsistency of current data. Some studies have demonstrated reduced mortality achieved by combination therapy [127][128][129][130][131][132], whereas the randomized multicentric comparison of two antibiotic regimens (meropenem vs. meropenem + moxifloxacin) in the treatment of severe sepsis and septic shock by Brunkhorst et al (Max-Sep study; [133]) found no superiority of combination treatment (meropenem + moxifloxacin) over monotherapy (meropenem) for severe sepsis. In this study, mortality 28 days after randomization was 23.9% (95%CI 19-29.4%) in the combination group and 21.9% (95%CI 17.1-27.4%) in the monotherapy group.…”
Section: Treatment Duration and Treatment Managementmentioning
confidence: 99%
“…To summarize, it must be stated that primary combination therapy of sepsis was never superior when the antibiotic used as monotherapy was a carbapenem. Moreover, in retrospective analyses it could be shown that in only about 30% of patients did the initial calculated antibiotic therapy actually encompass the pathogen, and de-escalation of therapy was only undertaken in a third of patients [127][128][129][130][131][132][133]. Combining broad-spectrum antibiotics simultaneously potentiates the selective pressure on pathogens and leads to increased development of resistance [134].…”
Section: Treatment Duration and Treatment Managementmentioning
confidence: 99%